Działalność nielegalnych organizacji młodzieżowych w latach 1945-1956 na terenie Żar = Illegal youth organisations in Żary in 1945-1956 - Bartkowiak, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Over the period of 1945-1956, in central-western Poland - as in other parts of the country - there were illegal youth organisations whose purpose was to show resistance to the communist authorities - a kind of natural defence mechanism put in motion by the growing oppressiveness of the state. They were mostly made up of secondary school students and also pupils in final years of primary schools, vocational schools students, working youth, and, occasionally, university students.
Keywords: Żary (woj. lubuskie); organizacje młodzieżowe; organizacje nielegalne; Polska - historia - od 1944 r.